KEPUASAN PELANGGAN TERHADAP PELAYANAN REFRAKSIONIS OPTISI OPTIK NAY DI SERANG BANTEN - Tituk Yuana Widiyati; Ferry Doringin (Jurnal Mata Optik, 2023)
This study aims to determine customer satisfaction with the service of Optical Refractionist at Optik Nay Serang Banten. The population in this study are consumers or customers at Optik Nay. This type of research is field research that uses facultative methods using a system of observation, interviews and documentation in the form of photos during the interview process. The sampling system used in this study is purposive, namely respondents who meet 3 criteria, namely patients or regular customers, adult age (30-50 years) and reactive respondents. The first step is to get 15 respondents and the second step is to sort out the results of the interviews, where the same opinion and response will be represented by one person and the researcher gets 6 respondents to be included in this study. Data analysis was carried out by comparing the results of interviews from 6 respondents. The results showed that the responses about RO services at Optik Nay from the six respondents were different, there were negative and positive responses.